Proceedings of the 1st International Symposium Innovations in Life Sciences (ISILS 2019) 2019
DOI: 10.2991/isils-19.2019.7
|View full text |Cite
|
Sign up to set email alerts
|

Development of Drugs for Treatment of Mortellaro’s Disease in Cattle

Abstract: The root cause of premature culling of animals from the herd as a result of diseases and injuries is a lesion of distal portions of limbs of an infectious etiology, which include Mortellaro's disease. Mortellaro's disease affects up to 60 percent of the cattle in Russia. BelNano was developed, consisting of liposomal fractions and nanoparticles of silver and copper distributed in its volume. The surface of the nanoparticles has been specially modified to provide high efficiency on the skin and keratinized tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Despite this, the antimicrobial activity against G+ and G- bacteria in Lange et al’s study and our study was similar. Research by Belyakova et al [ 45 ] indicated that CuNPs and AgNPs had antibacterial activity against Fusobacterium necrophorum , Treponema spp., and Borrelia spp. bacteria, which are etiological factors that lead to lameness.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the antimicrobial activity against G+ and G- bacteria in Lange et al’s study and our study was similar. Research by Belyakova et al [ 45 ] indicated that CuNPs and AgNPs had antibacterial activity against Fusobacterium necrophorum , Treponema spp., and Borrelia spp. bacteria, which are etiological factors that lead to lameness.…”
Section: Discussionmentioning
confidence: 99%